2017
DOI: 10.1002/hpm.2427
|View full text |Cite
|
Sign up to set email alerts
|

The contextual‐level effects of social trust on health in transitional countries: Instrumental variable analysis of 26 countries

Abstract: We analyse the effect of contextual-level social capital on health status in a sample of 26 transitional countries of Central and South Europe, Mongolia, and the former Soviet Union for 2006-2010 (N = 51 911). Contextual-level social capital is conceptualized as country-level social trust, while health status is conceptualized as self-rated health. We use ordinary least squares and instrumental variable regressions to address endogeneity and especially to rule out reverse causality. Both instrumental variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Please tell me on a scale from 0 to 10, where 0 means you can't be too careful and 10 means that most people can be trusted". Following the literature, individual responses averaged across communities will gauge the level of community social trust (Kim et al, 2011;Campos-Matos et al, 2015;Habibov and Cheung, 2018). The first Instrument, population density, is measured as persons/km2 and is taken from the International Database of the US Census Bureau (2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Please tell me on a scale from 0 to 10, where 0 means you can't be too careful and 10 means that most people can be trusted". Following the literature, individual responses averaged across communities will gauge the level of community social trust (Kim et al, 2011;Campos-Matos et al, 2015;Habibov and Cheung, 2018). The first Instrument, population density, is measured as persons/km2 and is taken from the International Database of the US Census Bureau (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In comparison, previous studies have concentrated on individual-level social trust only as they followed the tradition of conceptualizing social capital as the resources embedded within an individual's durable social network, and therefore the analysis was conducted at the individual level (Bourdieu, 1985;Lin, 1999;Arezzo and Giudici, 2017). However, the novelty of the concept of social capital lies in its collective, contextualized, area-level leverage (Kim et al, 2011;De Clercq et al 2012;Habibov and Cheung, 2018). This line of conceptualization originates from the work of Putnam (2000), who demonstrated that social capital plays a role in the public good at both the community and area levels.…”
Section: Theoretical Foundationmentioning
confidence: 99%